1984
DOI: 10.1016/s0022-5347(17)50510-8
|View full text |Cite
|
Sign up to set email alerts
|

Cystoscopic Fluorescence Detector for Photodetection of Bladder Carcinoma with Hematoporphyrin Derivative

Abstract: Hematoporphyrin derivative, a fluorogenic substance, tends to accumulate at higher levels in most tumor tissues after intravenous injection. These properties provide a potential application for the detection of malignant tumors. We report the development and in vitro evaluation of an instrument designed to excite and detect low levels of hematoporphyrin derivative fluorescence emitted by tumor cells in the bladder after hematoporphyrin derivative administration. The light source of the instrument for specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, there is interest in the use of fluorescence for detecting and quantifying tumour porphyrin levels (e.g. Lin et al, 1984;Lindley, 1989). It is therefore useful to relate porphyrin fluorescence with cellular inactivation following PDT.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is interest in the use of fluorescence for detecting and quantifying tumour porphyrin levels (e.g. Lin et al, 1984;Lindley, 1989). It is therefore useful to relate porphyrin fluorescence with cellular inactivation following PDT.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the reaction mechanisms leading to observable morphologic changes in cells are completely unknown. An observation of this type is the PDT-induced formation of giant cells in a bladder tumor cell line (Bellnier and Lin, 1984). The same investigators demonstrated recovery from HPD-photosensitized damage using a split-dose technique (Bellnier and Lin, 1985).…”
Section: Sensitization Of Microorganisms Cells and Organellesmentioning
confidence: 98%
“…Subsequently, Profio and Doiron (47) and JSinsey et al (48) pioneered the development of dedicated fluorescence instrumentation using photoelectronic detectors. This, and the initial clinical and animal model studies of HpD-mediated PDT by Dougherty and colleagues (49,50), led to fluorescence diagnostic studies by many other groups using this drug or its later commercial, oligomer-enriched form, Photofrin (QLT Phototherapeutics, Vancouver, Canada) (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64).…”
Section: Historical Backgroundmentioning
confidence: 99%